The Corporate Sepulchre In Frank Norris’s The Octopus: A Story Of California - R. Senthilkumar; Dr. R. Bharathi (Journal for ReAttach Therapy and Developmental Diversities, 2024)
This research paper tries to bring out the struggle of Californian wheat farmers in the San Joaquin Valley against the powerful Pacific and Southwestern Railroad Monopoly. The novel, The Octopus: A Story of California depicts the monopolistic, land-grabbing railroad, consolidation, organization, conformity, tough-minded, self-reliant people, exploited the land, subversion, coercion and outright violence. This novel is dealt with the tensions between the railroad, the ranchers and rancher’s league and also exhibits corporate greed, monopolistic power, exploitation of the working class, struggle between the labor and capital, the decline of the individual and the transformation of California.